Pregnancy does not adversely impact diagnostic tests for HTLV-1/2 infection - Rosadas, Carolina; Tosswill, Jennifer H.; Tedder, Richard; Taylor, Graham P. (PLOS Neglected Tropical Diseases, 2019)
Author summary Human T-cell lymphotropic virus (HTLV) can be transmitted from mother to child, mainly by breastfeeding. All preventive measures to avoid HTLV mother to child transmission depend on the identification of infected pregnant women. HTLV diagnosis is based on serological screening tests, confirmed by serology and/or molecular assays. The aim of the study was to verify whether pregnancy adversely impacts the identification of HTLV infection. Using paired samples from 21 women living with HTLV-1/2 obtained during pregnancy and while not pregnant we demonstrate that both serology and molecular assays perform equally well in both settings and can be use for the diagnosis of HTLV infection during pregnancy.